What and how do SMEs gain by going international? A longitudinal investigation of financial and intellectual resource growth - Li, Lei; Li, Dan; Goerzen, Anthony; Shi, Weilei (Stone) (Elsevier, 2018)
This study examines the accumulation of financial and intellectual resources of U.S.-based biopharmaceutical SMEs. We find that internationalized SMEs experience better financial resource growth than domestic market-focused SMEs only in the long run. While international expansion per se does not enable SMEs to accumulate more intellectual resources than via domestic expansion, it exerts a positive impact over time for SMEs with strong alliance capabilities. Moreover, we show that alliance capabilities are more important than in-house technological capabilities for key resource accumulation of internationalized SMEs over time. Our results infer that SMEs gain the benefits of resource exploration via international expansion.